Индивидуализации лечения блокаторами рецепторов ангиотензина II больных гипертрофической кардиомиопатией - Комиссарова, С.М.; Чакова, Н.Н.; Крупнова, Э.В.; Михаленко, Е.П.; Чеботарева, Н.В.; Ниязова, С.С. (Фактори експериментальної еволюції організмів, 2013)
Aims. To assess the influence of gene polymorphism, coding RAAS proteins (I/D gene polymorphism ACE and А1188С gene polymorphism AGTR1) on the effectiveness and safety of ARB therapy (losartan) in patients with HCMP. Methods. The study comprised 73 patients with HCMP (54 males and 19 females, mean-age 46,7±15,7 yrs.). All patients received losartan during 12 months. All patients showed I/D- polymorphism in АСЕ gene and change in А1166С of gene AGTR1 using PCR-RFLP analysis. Results. Losartan therapy improved hemodynamic state in HCMP patients, but was unevenly effective in respect of left ventricular hypertrophy regression (LVH). The greatest positive effect of treatment was noted in most of the patients (87,5 %) that were the carriers of heterozygous genotype combination АС(AGTR1)/ID(ACE) and in 58,3 % of carriers of homozygous genotypes АА(AGTR1)/DD(ACE). In subjects with genotype combination of AA(AGTR1)/II ACE a resistant LVH was discovered in в 87,5 % of cases. Conclusion. Prior to losartan therapy, it is reasonable to perform genotyping of RAAS proteins (I/D gene polymorphism ACE and А1188С gene polymorphism AGTR1), which allows considering genetic factors susceptible to the drug administered.

Key words: hypertrophic cardiomyopathy, AGTR1 and ACE gene polymorphism, angiotensin II beta-blocker.